Spatial Visualization Tasks To Support Students' Spatial Structuring In Learning Volume Measurement - Shintia Revina; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo; Frans van Galen (Journal on Mathematics Education, 2011)
Many prior researches found that most of students in grade five tended to have difficulty in fully grasping the concept of volume measurement because they have to build their competence in spatial structuring. The unit of volume packing measurement must be integrated and coordinated in three-dimension. On the other hand, it is revealed the errors that students made on the volume measurement tasks with threedimensional cube arrays are related to some aspects of spatial visualization, such as the skill to "read off" two-dimensional representation of solid objects. For those reasons, this research is aimed to develop classroom activities with the use of spatial visualization tasks to support students' spatial structuring in learning volume measurement. Consequently, design research was chosen as an appropriate means to achieve this research goal. In this research, a sequence of instructional activities is designed and developed based on the hypothesis of students' learning processes. This research was conducted in grade 5 of SD Pupuk Sriwijaya Palembang, Indonesia.Keywords: volume measurement, spatial structuring, spatial visualization, design research.